Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Profitabilitas Dengan Intellectual Capital Sebagai Pemoderasi - Sari, Putu Ratih Puspita; Dwirandra, Anak Agung Ngurah Bagus (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
Profitability describes the ability of companies to generate profits through sales, asset, and capital. To Increase the profitability of the company has always faced by the trade-off between profitability and liquidity, and leverage. This study aimed to determine the effect of the current ratio (CR) and debt to equity ratio (DER) on the profitability of the intellectual capital (IC) as a moderating. The study was conducted on 47 property companies listed in Indonesia Stock Exchange in 2014-2016. The sample was selected using purposive sampling technique that was selected 34 ompanies, but found four companies with observations outliers that eliminated from the sample. Selected samples were analyzed using MRA. The results prove that CR negative effect, while DER positive effect on profitability. IC act as a pure moderating variable which is weaken the negative influence CR and strengthen the DER positive influence on profitability. Keywords: current ratio, debt to equty ratio, intellectual capital, profitability